2017
DOI: 10.1016/j.bjid.2017.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the ACC/AHA and Framingham algorithms to assess cardiovascular risk in HIV-infected patients

Abstract: The aim of this study was to compare the predictions of Framingham cardiovascular (CV) risk score (FRS) and the American College of Cardiology/American Heart Association (ACC/AHA) risk score in an HIV outpatient clinic in the city of Vitoria, Espirito Santo, Brazil. In a cross-sectional study 341 HIV infected patients over 40 years old consecutively recruited were interviewed. Cohen's kappa coefficient was used to assess agreement between the two algorithms. 61.3% were stratified as low risk by Framingham scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…On the other hand the studies that used kappa statistic, the range of values was 0.22 (fair agreement)–0.78 (substantial agreement). In the HIV-infected populations, two studies 40 , 41 used kappa to test agreement between FRS and ASCVD algorithms with values of 0.61 and 0.75 falling in the substantial agreement category. The other study 42 used prevalence bias adjusted kappa (PABAK) and found no statistical difference in risk scores between tools.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand the studies that used kappa statistic, the range of values was 0.22 (fair agreement)–0.78 (substantial agreement). In the HIV-infected populations, two studies 40 , 41 used kappa to test agreement between FRS and ASCVD algorithms with values of 0.61 and 0.75 falling in the substantial agreement category. The other study 42 used prevalence bias adjusted kappa (PABAK) and found no statistical difference in risk scores between tools.…”
Section: Discussionmentioning
confidence: 99%
“…They highlight that the models with best performance in Latin America are Framingham and ASCVD. Some studies with HIV populations have been reported from Brazil, although with small sample size and short follow-up [24][25][26][27] .…”
Section: Discussionmentioning
confidence: 99%
“…Since earlier studies suggested that the existing cardiovascular disease risk scores may inaccurately estimate the risk of clinical events in HIV population, more recent publications have attempted to confirm and extend this work [103, 104, 105•, 106112]. There remains conflicting data about how well Framingham and other non-HIV-specific algorithms predict cardiovascular disease risk with some studies showing good discrimination or calibration [104, 106] and others, less so [105•, 106, 107, 109, 110].…”
Section: Cvd Risk Assessment and Novel Cvd Risk Factors In Hivmentioning
confidence: 92%